A standardised terminology of the embryonic envelopes and associated developmental stages of tapeworms (Platyhelminthes: Cestoda) - Conn, David Bruce; Swiderski, Zdzisław (Folia parasitologica, 2008)
Over the past 40 years, much has been published on the ultrastructure and cellular development of embryonic structures in a wide range of cestodes. However, the literature contains many discrepancies in both terminology and interpretations because of the facts that these organisms are phylogenetically diverse within their respective orders and families, the habitats that affect embryonic envelope structure are diverse, and the work has been done in various laboratories around the world. This review and synthesis was initiated by a working group of biologists from around the world convened at the Fifth International Workshop on Cestode Systematics and Phylogeny in Ceské Budejovice, at the Institute of Parasitology of the Biology Centre, Academy of Sciences of the Czech Republic. It brings together the data from published work and establishes a uniform terminology and interpretation based on the data as they are presented. A consensus was reached for standardised definitions of the oncosphere, hexacanth, coracidium, embryonic envelopes, outer envelope, inner envelope, embryophore, vitelline capsule, shell, and outer coat. All of these are defined as components of the embryo or its vitellocyte-derived or uterine-derived coatings.
Keywords: ploštěnci; terminologie jako téma; Terminology as Topic; Platyhelminths; Animals; zvířata